Considerações sobre memória afetiva alimentar na orientação dietética para o idoso - Santos, Tânia Rodrigues dos (2019)
This thesis discusses the relationship between the aging process, old age and alimentary affective memory , making it the guiding axis of clinical practices in the field of Nutrition. The dietary guidance focus for the elderly has brought to light issues and referrals pertinent to the construction of healthy eating habits, based on the recognition that: they exceed the dimension of need, are linked to pleasure and have a strong ethnographic connection with family and social environment. The theme is relevant, not only because we live in a time when the demographic and nutritional transitions impact the habits and health conditions of the population, but also because it refers to an achievement that, as well as in the subjective plane, demands to live more time and with more quality. With aging of the population aging and the growth of the number of nutritionists/ dietitians, it becomes more necessary that the latter understand in greater depth the biopsychosocial determinants of the aging process, subverting the dominant tendency to adopt a biological point of view on life and health . In this perspective, the general objective of this work was to show that the eating habits of the elderly are related to positive and / or negative feelings updated when they need a dietary guidance. In turn, its specific objectives were: (1) to review the pertinent literature in order to identify if and how elderly problematize the affective, social and cultural relationship with the foods they eat; (2) to reflect on the dietary behavior recommended in the Medical Guidelines (often taken as reference in the field) and their relationship with the concepts of active aging and integrality in care; and (3) to emphasize the importance for nutritionists/ dietitians, of the adoption of subjectively oriented listening for elderly patients, assuring them adequate nutritional management. From a methodological point of view, this thesis was composed by a literature review on relevant topics to reflection (which can be found in the two initial chapters) and a Clinical Case Study, understood as a fertile field to bring to light the practice of a nutritionist/ dietitian and the issues raised by the care of the elderly. The results obtained in the Case Study allowed us to reflect on the impasses faced in the clinical exercise, which, from my point of view, can contribute not only to my professional improvement, but also to the formation of new nutritionists/ dietitians, since it allowed to conclude that the effective dietary guidance of the elderly should be supported by a listening of facts and food memories that can instruct behaviors and increase their adherence to diet